The relationship between ethnic group affiliation (EGA) and willingness to communicate (WTC) in English among undergraduates in a public university in Malaysia - Abd Razak, Fatin Nabila; Hossein, Vahid Nimehchisalem; Abdullah, Ain Nadzimah (Australian International Academic Centre (AIAC), 2018)
This study aimed to examine the relationship between ethnic group affiliation (EGA) and Willingness to Communicate (WTC) in English among the undergraduates in a public university in Malaysia. The three ethnic groups involved in the study were Malays, Chinese, and Indians. An EGA questionnaire was adapted from Phinney (1992), Magid (2004), and Gatbonton and Trofimovich (2008), while a WTC questionnaire was adapted from McCroskey (1992), Fishman (1972), and Granhemat (2015). The questionnaires were distributed to 39 participants representing the three major races. The analysis showed that the level of EGA for the Malays was the highest with 83% as compared to the Chinese with 73% and the Indians with 81%. Meanwhile, the level of WTC of the Chinese received the highest score of 75%, while the Malays and the Indians were at 63%. Results of the Pearson Correlation, r= -0.323, p= 0.045, indicated a significantly weak and negative association between EGA and WTC. This implicated that high levels of EGA would result in low levels of WTC. Hence, in addressing that, attention needs to be given to the aspect of EGA in language learning and teaching approaches in order to achieve better language proficiency among the English language learners in Malaysia.